A combination of autoantibodies to cyclic citrullinated peptide (CCP) and HLA-DRB1 locus antigens is strongly associated with future onset of rheumatoid arthritis - Berglin, Ewa (BioMed Central, 2004)
Antibodies against cyclic citrullinated peptide (CCP) and rheumatoid factors (RFs) have been demonstrated to predate the onset of rheumatoid arthritis (RA) by years. A nested case–control study was performed within the Northern Sweden Health and Disease study cohort to analyse the presence of shared epitope (SE) genes, defined as HLA-DRB1*0404 or DRB1*0401, and of anti-CCP antibodies and RFs in individuals who subsequently developed RA. Patients with RA were identified from among blood donors whose samples had been collected years before the onset of symptoms. Controls matched for age, sex, and date of sampling were selected randomly from the same cohort. The SE genes were identified by polymerase chain reaction sequence-specific primers. Anti-CCP2 antibodies and RFs were determined using enzyme immunoassays. Fifty-nine individuals with RA were identified as blood donors, with a median antedating time of 2.0 years (interquartile range 0.9–3.9 years) before presenting with symptoms of RA. The sensitivity for SE as a diagnostic indicator for RA was 60% and the specificity was 64%. The corresponding figures for anti-CCP antibodies were 37% and 98%, and for RFs, 17–42% and 94%, respectively. In a logistic regression analysis, SE (odds ratio [OR] = 2.35), anti-CCP antibodies (OR = 15.9), and IgA-RF (OR = 6.8) significantly predicted RA. In a combination model analysis, anti-CCP antibodies combined with SE had the highest OR (66.8, 95% confidence interval 8.3–539.4) in predicting RA, compared with anti-CCP antibodies without SE (OR = 25.01, 95% confidence interval 2.8–222.2) or SE without anti-CCP antibodies (OR = 1.9, 95% confidence interval 0.9–4.2). This study showed that the presence of anti-CCP antibodies together with SE gene carriage is associated with a very high relative risk for future development of RA.